Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1161/str.50.suppl_1.wp11
|View full text |Cite
|
Sign up to set email alerts
|

Abstract WP11: Semi-automated Quantitative Assessment of Reperfusion in Acute Ischemic Stroke Patients

Abstract: Introduction: Accurate assessment of brain reperfusion during endovascular treatment helps determining whether adjuvant intervention is necessary. The gold standard for reperfusion scales are the modified and extended Treatment in Cerebral Ischemia (mTICI and eTICI) scale. However, these scales are coarse and highly dependent on the observer, which may result in imprecise rating of reperfusion status. In this study, we developed a semi-automated quantitative reperfusion measure (qTICI) that was bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…10 An OR for EVT effect modification due to ICV (OR:0.98 [95%CI:0.881-1.091] per 10 mL) and MMR (OR:1.010[95%CI:0.994;1.026]) per one point change) were used for baseline simulations. Since these ORs were based on CTPs from trials published between 2015 and 2017 with limited brain coverage, 10,25 the ORs and 95%CIs for effect modification were altered by -0.1 and -0.05 for ICV, and +0.1 and +0.05 for MMR to consider technological improvements in CTP software. Finally, we simulated the most favorable CTP-based EVT patient selection PSA scenario considering patients aged ≥80 years, a 0.3 decrease of the EVT effect OR (OR:1.37[95%CI:0.91-2.0]), and a 0.1 decrease of the ICV or MMR based EVT effect modification (OR:0.88[95%CI:0.781-0.991]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 An OR for EVT effect modification due to ICV (OR:0.98 [95%CI:0.881-1.091] per 10 mL) and MMR (OR:1.010[95%CI:0.994;1.026]) per one point change) were used for baseline simulations. Since these ORs were based on CTPs from trials published between 2015 and 2017 with limited brain coverage, 10,25 the ORs and 95%CIs for effect modification were altered by -0.1 and -0.05 for ICV, and +0.1 and +0.05 for MMR to consider technological improvements in CTP software. Finally, we simulated the most favorable CTP-based EVT patient selection PSA scenario considering patients aged ≥80 years, a 0.3 decrease of the EVT effect OR (OR:1.37[95%CI:0.91-2.0]), and a 0.1 decrease of the ICV or MMR based EVT effect modification (OR:0.88[95%CI:0.781-0.991]).…”
Section: Methodsmentioning
confidence: 99%
“…The regression analyses for EVT effect modification due to CTP estimated ICV and MMR by Campbell et al were repeated as the initial work only reported p-values (full analyses in Online supplement D). coverage,10,25 the ORs and 95%CIs for effect modification were altered by -0.1 and -0.05 for ICV, and +0.1 and +0.05 for MMR to consider technological improvements in CTP software. Finally, we simulated the…”
mentioning
confidence: 99%